Las revelaciones contables en las empresas productivas de la ciudad de Latacunga, durante el periodo enero-diciembre 2011. - Tonato Conterón, Ana Rocío (2014)
The research has as its objective to establish a clear and sustained knowledge about the Accounting Disclosures in the companies of Latacunga city, specifically for firms carrying on productive activities. In particular the main objective has been to detect errors in the related parties involved as well as in financial transactions conducted in conjunction with the backlog that produce those outstanding balances in an accounting adjustment at the end of an ordinary period of accounting operations, of course with the help of the current regulations and the efficient application of international accounting standards. On the basis of regulations issued by the IASB, so the resolutions of the Superintendence of Companies from Ecuador and other considerations to take into account when applying the notes to the Financial Statements in these businesses. This thesis has been developed through the application of research methods which allowed responding to posed guidelines questions to conduct a situational analysis that reflects the reality. The adoption of the new regulations for companies that carry out their activities in this sector, it’s an aid to the accounting professionals and the respective managements, the questions that may arise in the implementation process at the time of drawing up the respective notes to the financial implementation,